The Role of Zakat Collection Unit (UPZ) as an Effort to Increase ZIS Collection in BAZNAS of West Java Province - Zettira Dzilkhaira, Nabila (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2025)
The collection of zakat, infaq, and shadaqah (ZIS) funds is a vital aspect in the operation of social institutions, especially BAZNAS West Java Province. In an effort to increase the effectiveness if collection, innovation is the key to attracting public interest and trust as muzakki. The establishment of the Zakat Collection Unit (UPZ) is one of the strategic innovations implemented to expand the reach and strengthen the efficiency of ZIS fund collection. This study aims to analyze the role of UPZ in increasing ZIS fund collection in BAZNAS West Java Province in 2022. Using a field research approach and descriptive analysis methods, the main focus is on the contribution of UPZ to the total ZIS fund collection, as well as the factors that affect its effectiveness. The results of the study show that UPZ has a very significant contribution, reaching 80.7% of the total ZIS fund collection in 2022. This figure confirms the vital role of UPZ as the most important guard in the collection of ZIS. Factors that support the success of UPZ include closeness to the community, effective socialization efforts, transparent fund management, and ease of access for muzakki to fulfill ZIS. In addition, UPZ also plays a role in increasing public awareness of the importance of ZIS and ensuring the distribution of ZIS funds that are right on target. Thus, this study concludes that UPZ is a crucial element in the fundraising strategy of ZIS BAZNAS West Java Province. Strengthening capacity and continuous support for UPZ will further increase the effectiveness of collection and have a positive impact on the welfare of the community.